Membangun Kesadaran Siswa Terhadap Dampak Bullying ‎Melalui Sosialisasi KKN di SDN 19 Padang Cermin Desa ‎Durian - Wijaya, Edo; Komariah , Nur ‎; MaiIantika ‎; Bella Satiyo Putri; Faridha Noer Barkah (WISE Pendidikan Indonesia, 2025)
The phenomenon of bullying in elementary schools remains a serious issue that significantly affects students’ psychological, social, and academic development. This study aims to enhance students awareness of the impacts of bullying through a Community Service Program (Kuliah Kerja Nyata) conducted at SDN 19 Padang Cermin, Durian Village, Pesawaran Regency. A descriptive qualitative approach was employed, utilizing observation, interviews, and documentation to obtain an in-depth understanding of students’ behavioral and attitudinal changes following the program. The findings reveal that the KKN-based socialization effectively increased students’ comprehension of bullying forms and consequences, fostered social empathy, and promoted respectful interactions within the school environment. Students demonstrated high levels of enthusiasm, particularly during discussion and empathy simulation sessions, indicating that participatory methods are effective in cultivating moral values and positive character development from an early age. Moreover, this program reinforced collaboration among university students, teachers, and the local community in creating a safe, inclusive, and violence-free learning environment.